Evaluation of anti-malarial activity of Artemisia turcomanica and A. kopetdaghensis by cell-free β-hematin formation assay - M. Mojarrab; S.A. Emami; Sh. Gheibi; A.M. Taleb; F. Heshmati Afshar (Iranian Society of Pharmacognosy, 2016)
Background and objectives:The plants of genus Artemisia (Asteraceae) have been conventionally used for prevention and medication of a number of ailments. In the present research, ten extracts with different polarities from aerial parts of two Artemisia species, A. kopetdaghensis and A. turcomanica were evaluated for their potential anti-malarial properties. Methods: The plant materials were extracted successively with petroleum ether (PE), dichloromethane (DCM), ethyl acetate (EtOAC), ethanol, and ethanol-water (1:1 v/v)  by cold maceration method. Cell free β-hematin formation assay were used for assessing anti-malarial activity of obtained extracts. Results: DCM extract of A. kopetdaghensis and PE extract of A. turcomanica showed remarkable anti-malarial activity with IC50 values of 1.04±0.02 mg/mL and 0.90±0.27 mg/mL, respectively, compared to positive control (chloroquine, IC50 0.04±0.01 mg/mL). Conclusion:  It seems that the anti-malarial activity of these extracts might be bound up with the presence of compounds with low or medium polarity; hence, this preliminary test indicated that these potent extracts could be considered for further investigations to find new sources of anti-malarial phytochemicals.